From Regional to Intercontinental Trade: The Successive European Trade Empires from the Sixteenth to the Eighteenth Century in Asia - Sami Bensassi (Economics and Econometrics Research Institute (EERI), 2010)
For a very long time, the areas available for continuous long-distance trade were limited to territories the size of Braudel's Mediterranée (1949). Whatever the commercial organizations (merchants in the Roman or the Fatimid Empires, the Hanseatic League, the Florentine Companies), their trade was not able to directly handle branches more than a month's sailing from their main base (in the best conditions). During the three centuries after Vasco de Gama had reached India, European trading areas dramatically expanded to the shores of Asia, and a long period of harsh competition set the East India Companies of the main European powers of the time against one another. This paper intents to provide answers to two questions: what were the elements that allowed these companies to maintain transactions over such vast areas? And why were some of these companies far more successful than the others? To answer these two questions we have available extensive literature covering the intersection of history, business and economy, generally focusing on one company or on a particular aspect of trade (Chauduri, 1978; Israel, 1989; Subrahmanyan, 1993; Ames, 1996). Our task will be to briefly review these sources, to extract information from them and to compare the economic adaptations and innovations that allowed these companies to be the greatest of their time.
Keywords: B52; F02; N70; 330; European Trade Empires; Estado da Índia; Dutch East India Company; English East India Company